PENDIDIKAN KARAKTER DALAM KITAB ADABUL ALIM WAL MUTA'ALIM KARYA KH. HASYIM ASY'ARI: SCOPING REVIEW - Ma'arif, Samsul; Muhid, Abdul (Al’ulum Jurnal Pendidikan Islam, 2025)
Character education is an important pillar in forming a whole human being who is not only intellectually intelligent, but also moral and spiritual. The reality of education today shows a tendency that still focuses on cognitive aspects, while character aspects have not received adequate attention. This study aims to examine the values of character education in the book Adabul 'Alim wal Muta'allim by KH. Hasyim Asy'ari and examine its relevance to the needs of contemporary Islamic education. The method used a scoping review of 25 scientific articles obtained through a systematic literature search using focused keywords. The results of the study show that this book contains the values of adab, including relationships with God, self, teachers, and knowledge. Values such as sincerity, responsibility, patience, tawadhu', and discipline become the core of the character-building process in education. In conclusion, this book provides a strong foundation and a major contribution to the development of integral, applicable, and sustainable character education in the Islamic education system, and can be used as a reference in strengthening adab-based education in various Islamic educational institutions, both formal and non-formal, through habituation and exemplary approaches.